Moderate oral supplementation with docosahexaenoic acid improves platelet function and oxidative stress in type 2 diabetic patients - Véricel, Evelyne; Colas, Romain; Calzada, Catherine; Lê, Quang Huy; Feugier, Nathalie; Cugnet, Christine; Vidal, Hubert; Laville, Martine; Moulin, Philippe; Lagarde, Michel (Thrombosis and Haemostasis, 2015)
Platelets from patients with type 2 diabetes are characterised by hyperactivation and high level of oxidative stress. Docosahexaenoic acid (DHA) may have beneficial effects on platelet reactivity and redox status. We investigated whether moderate DHA supplementation, given as a triglyceride form, may correct platelet dysfunction and redox imbalance in patients with type 2 diabetes. We conducted a randomised, double-blind, placebo-controlled, two-period crossover trial (n=11 post-menopausal women with type 2 diabetes) to test the effects of 400 mg/day of DHA intake for two weeks on platelet aggregation, markers of arachidonic acid metabolism, lipid peroxidation status, and lipid composition. Each two week-period was separated from the other by a six-week washout. Daily moderate dose DHA supplementation resulted in reduced platelet aggregation induced by collagen (-46.5 %, p< 0.001), and decreased platelet thromboxane B2 (-35 %, p< 0.001), urinary 11-dehydro-thromboxane B2 (-13.2 %, p< 0.001) and F2-isoprostane levels (-19.6 %, p< 0.001) associated with a significant increase of plasma and platelet vitamin E concentrations (+20 % and +11.8 %, respectively, p< 0.001). The proportions of DHA increased both in plasma lipids and in platelet phospholipids. After placebo treatment, there was no effect on any parameters tested. Our findings support a significant beneficial effect of low intake of DHA on platelet function and a favourable role in reducing oxidative stress associated with diabetes.
Keywords: Platelet aggregation; arachidonic acid; vitamin E; isoprostane; plasma and platelet lipid composition